Comparison of dexmedetomidine with propofol for sedation in critically ill adult patients - Subedi, Deepika; Shrestha, Anil; Shrestha, Pramesh Sunder; Sigdel, Shailendra; Pradhan, Bishwas (Journal of Chitwan Medical College, 2021)
Background: Patients in intensive care unit setting require invasive monitoring and treatments that often lead to anxiety and pain. To reduce anxiety, increase tolerance and improve outcome of such interventions, sedation is common practice. Propofol and Dexmedetomidine both are frequently used for sedation in ICU. Methods: In a randomized, prospective, open label study, seventy critically ill adult patients requiring mechanical ventilation were assigned to receive either propofol infusion with 1.2 mg/ kg/hr or dexmedetomidine infusion with 0.2 mcg/kg/hr starting dose within twelve hours of intubation and titration of study drug to achieve Richmond agitation sedation score (RASS) of -2 to 0 until extubation or for seven days whichever was longer. Primary end point was percentage of time within target sedation range and secondary end points were prevalence of delirium, duration of mechanical ventilation and use of fentanyl and haloperidol. Results: The percentage of time within target sedation range (Richmond agitation sedation score -2 to 0) was similar (p=0.947). Consumption of median dose of fentanyl (p=0.043) and haloperidol (p=0.025) were less in dexmedetomidine group. Ability to communicate pain via visual analogue scale was significantly higher in dexmedetomidine group 28 (80%) as compared to propofol group 14 (40%); p=0.001. Adverse events like hypotension, bradycardia was not significantly different. Conclusions: Sedation with dexmedetomidine was similar as compared to propofol in mechanically ventilated critically ill adult patients. Dexmedetomidine reduced duration of delirium consumption of fentanyl and improved patients’ ability to communicate pain compared to propofol.